Guiding Directions in Social Entrepreneurship and Innovation Education: Experts' Insights - Marzena Starnawska (Jesuit University Ignatianum in Krakow, 2019)
RESEARCH OBJECTIVE: The aim of this paper is to provide insights into the views of SE and SI experts from different settings on university education in these two fields. THE RESEARCH PROBLEM AND METHODS: SEE 1 has been gaining significant interest following development of the research field. However, literature is scarce in this area, and the empirical work on SEE is almost nonexistent. The research is based on the SE and SI ecosystem development projects run by two neighbouring cities in Poland. Using inductive approach, the author presents qualitative data from group discussions and semi-structured interviews among experts from different settings. Grounded theory methods are used to generate key categories representing direction for SEE and SIE development. THE PROCESS OF ARGUMENTATION: Based on review of literature and analysis of gathered data, the author provides key guiding directions for SEE and SIE development. First, their main features emerging from literature are presented. Next, the research design and key findings are presented. RESEARCH RESULTS: Research results indicate the need for encompassing approach when designing key directions for SE and SI education. CONCLUSIONS, INNOVATIONS, AND RECOMMENDATIONS: The findings show that SEE should be extended beyond business school environment. Also, educational model should be constantly refined in response to stakeholders' needs, also academia should include community and other stakeholders, also from other fields and disciplines. The engaging approach in educational setting draws attention to university contexts, expose SEE to local problems and construct them accordingly. Also, SEE requires significant efforts in promoting SE phenomenon and the education itself, to gain legitimacy and engage dedicated individuals and organizations.